Análise das ementas e bibliografias das disciplinas de educação infantil dos currículos de Educação Física no estado do Tocantins - Varão, Hava Dias (Universidade Federal do Tocantins, 2023)
The present work analyzed the bibliographical menus of the disciplines of Early Childhood Education in the curricula of the degree courses in Physical Education in the State of Tocantins. Characterizing it as a documentary research, which we used the Iramuteq instrument for data analysis, from the result a dialogue was raised regarding the curricula of the courses with the literature of the authors who discuss the culture of childhood. Thus, the analysis of the curricula revealed some points of divergence, highlighting gaps in the curriculum of Early Childhood Education subjects. From the information recorded, we evidenced that the Licentiate curriculum of the Physical Education course in the State of Tocantins needs to be restructured according to the latest changes in Resolutions 06/2018 and 02/2019, both of the National Council of Education. It is emphasized that there is a need to strengthen teacher training in dialogue with the demands of the professional field. Early Childhood Education requires us to problematize the traditional biologicist view, expanding the theoretical-practical discussions of future teachers for the recognition of the child as a subject of rights, recognizing their capacity for cultural production and their ways of appropriating knowledge in the context of early childhood education.